Improvement in pharmacists' knowledge through professional inservice education programs - (:unkn) unknown (My University, 2004)
Continuing Education programs are not mandatory for pharmacists in Turkey. As a model, we conducted a program, "Good Pharmacy Practice", to evaluate the benefit to pharmacists and improvement in their knowledge with professional inservice education programs. Each pharmacist completed a multiple choice test (50 questions) just before (pre-test) and at the end (post-test) of the six-day (totally 40 hours) education program. Attendants were not requested to provide their name or initials on the test. The questions were prepared by the lecturers. Totally 95 pharmacists (92% retail pharmacists, 38% male, mean age ± SD 37.6 ± 10.1) attended the program. The tests were scored over 100 total points. The mean score (± SD) of post-test (56.6 ± 10.3) was considerably higher than that of pre-test (36.1 ± 7.85). Only 3.2% of the attendees were successful (scored over 50%) at the pre-test. However, the rate of success improved significantly at the post-test, to 77.8%. Professional inservice education programs can be beneficial for pharmacists, especially to keep their knowledge current and to review essential information previously learned.
Keywords: Improvement in knowledge; Pharmacist education; Professional Inservice Education